Hybrid Taguchi–Fuzzy‐based performance‐exhaust emission trade‐off study of variable compression ratio diesel engine fueled with undi‐diesel blends. Issue 2 (22nd August 2019) - Madane, Pravin A.; Bhowmik, Subrata; Panua, Rajsekhar
Abstract: The present investigation highlights the effect of variable compression ratio (VCR) on the performance and exhaust emission characteristics of a single cylinder, direct injection diesel engine fueled with undi‐diesel blends. 10%, 20%, 30%, 40%, and 50% undi fuel have been added to diesel in volumetric proportions and tested by varying compression ratio (CR) from 16:1 to 20:1. Undi addition to diesel fuel significantly improves the brake thermal efficiency (BTE) and brake specific energy consumption (BSEC) of the engine. In addition, higher CR facilitates to improve unburned hydrocarbon (UHC), carbon monoxide (CO) and smoke opacity of the diesel engine with the penalties of higher oxides of nitrogen (NOX ) emissions. In perspective of the engine experimental outputs, a Taguchi assisted Fuzzy based trade off study has been conducted to screen and locate the optimal diesel engine operating conditions, namely, CR, undi share, and load. The optimum process parameter has been found to be A2 B6 C2 with a multi performance characteristics index (MPCI) value of 0.683 indicating the optimum operating conditions of 17:1 CR, 50% (by volume) undi share at 50% load.